Morphopragmatic Analysis of Word Derivation Variations in the Holy Quran and their Translations into English - Khalaf , Abed Shahooth; Ali , Ayad Hamad; Ibraheem, Fatin Khalil; Rashid , Sabariah Md (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to examine the effect of variations in word derivations in the Holy Quran on conveying their communicative impact when translated into English. Specifically, the study seeks to identify which of the selected translations have preserved the intended pragmatic effect triggered by word derivation variations in each Ayah when translated into English. Methods: To achieve this objective, the study compiles a corpus consisting of Ayahs containing randomly selected morphological derivation variations from the Holy Quran and their translations in English by Ali (1934), Pickthall (1930), Ghali (1996), Arberry (1955), Palmer (1947), and Al-Hilali and Khan (1984). The content analysis method was employed to identify instances of word derivation variations in the corpus, and Nida’s (1964) principle of equivalent effect was adopted to examine the loss of the communicative impact of these words in each translation. Results: The findings of the study indicate that almost all the selected translations failed to preserve the intended pragmatic effect triggered by the variation in word derivations in the Holy Quran when conveyed to English recipients. Conclusions: The reasons behind this failure might be attributed to the translators' inability to grasp the intended pragmatic implications resulting from morphological variations of words.